2022
DOI: 10.3389/fmed.2022.991873
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double-blind clinical study in patients with COVID-19 to evaluate the safety and efficacy of a phytomedicine (P2Et)

Abstract: BackgroundIt has been proposed that polyphenols can be used in the development of new therapies against COVID-19, given their ability to interfere with the adsorption and entrance processes of the virus, thus disrupting viral replication. Seeds from Caesalpinia spinosa, have been traditionally used for the treatment of inflammatory pathologies and respiratory diseases. Our team has obtained an extract called P2Et, rich in polyphenols derived from gallic acid with significant antioxidant activity, and the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In a study mirroring observations in the MHV-A59 mouse model, both P2Et extract and Anamu SC were found to inhibit COVID-19 viral replication in Vero E6 cells from patient isolates. A Phase II clinical trial in COVID-19 patients treated with P2Et demonstrated a 2.7 day earlier hospital discharge compared to the placebo group, accompanied by a significant reduction in pro-inflammatory cytokines [ 20 ]. These findings suggest that these natural extracts, particularly P2Et, can effectively treat human coronavirus infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study mirroring observations in the MHV-A59 mouse model, both P2Et extract and Anamu SC were found to inhibit COVID-19 viral replication in Vero E6 cells from patient isolates. A Phase II clinical trial in COVID-19 patients treated with P2Et demonstrated a 2.7 day earlier hospital discharge compared to the placebo group, accompanied by a significant reduction in pro-inflammatory cytokines [ 20 ]. These findings suggest that these natural extracts, particularly P2Et, can effectively treat human coronavirus infections.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments using Vero E6 cells revealed a significant inhibition of viral replication by both extracts. Subsequently, a phase II multicentric randomized, double-blind clinical trial was conducted to assess the impact of P2Et treatment on clinical outcomes and immunological response in COVID-19 patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In mice injected with bleomycin, P2Et also decreased lung inflammation, fibrosis, and replication of human coronaviruses in vitro, showing its antiviral activity and anti-inflammatory capacity, two essential mechanisms to control the disease. 184 …”
Section: Medicinal Plants For Covid-19 Treatmentmentioning
confidence: 99%
“…The central research area of our group is the study and development of phytomedicines from Colombian plants, among them Petiveria alliacea (P. alliacea), Caesalpinia spinosa (C. spinosa), Tillandsia usneoides (T. usneoides), and Piper nigrum (P. nigrum) (Lasso et al, 2018;Urueña et al, 2020;Lasso et al, 2022;Urueña et al, 2022). Each one of the extracts of these plants has been characterized from a chemical point of view, and the main compounds have been isolated and studied.…”
Section: Immunomodulationmentioning
confidence: 99%
“…The extracts are standardized to be developed as botanical drugs due to their interesting antitumor and immunomodulatory activity in animal models (Lasso et al, 2018;Urueña et al, 2020). C. spinosa has also been studied in normal individuals to assess its safety and in coronavirus disease 2019 (COVID-19) patients, where significant biological activity has been demonstrated (Duran et al, 2022;Urueña et al, 2022).…”
Section: Immunomodulationmentioning
confidence: 99%